ANALYSIS OF COMPLICATIONS AFTER SUBTALAR ARTROEREISIS IN PATIENTS WITH PLANOVALGUS DEFORMITY - S. K. Tamoyev; N. V. Zagorodniy; V. G. Protsko; E. M. Sultanov; Z. K. Khamokov; B. G. Butayev (Travmatologiâ i Ortopediâ Rossii, 2011)
The results of observation of 9 patients after subtalar arthroereisis with developed different complications from 2008 to 2011 were presented. In 7 patients subtalar arthroereisis was held in conjunction with surgical correction of forefoot, in 2 patients was carried out in isolation. All complications were divided into 4 groups: talar sinus syndrome, the migration of subtalar implant, overcorrection of deformation, the subtalar implant destruction. Development of talar sinus syndrome after subtalar arthroereisis was associated with the using of too large implant. The implant migration was associated with failure to topographical requirements for its installation, as well as the inadequate size of it. Overcorrection of deformation was observed in cases where the subtalar implant was introduced deeper than the required. In cases of migration of implant «Vilex» its reimplantation was performed, while in other cases the implant was removed to eliminate the pain. In order to prevent complications after subtalar arthroereisis the topography of the subtalar implant in the sinus area and adhearance to the technology should take into account.